2008
DOI: 10.1507/endocrj.k07e-004
|View full text |Cite
|
Sign up to set email alerts
|

Increased Bone Turnover in Patients with Hypercholesterolemia

Abstract: Abstract. Osteoporosis has been linked with arteriosclerotic vascular diseases, suggesting that hypercholesterolemia or dyslipidemia may be a common pathogenetic factor underlying these diseases. However, little is known about the relationship between osteoporosis and hypercholesterolemia. The purpose of this study was, therefore, to investigate the effects of hypercholesterolemia upon bone metabolism, by measuring bone turnover markers in hypercholesterolemic patients. This study included 281 Japanese patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
2
29
2
1
Order By: Relevance
“…In our clinical studies, we observed that postmenopausal women with hypercholesterolaemia showed increased bone Acta Pharmacologica Sinica npg turnover and lower BMD, which is consistent with the data reported in other clinical studies [2][3][4] . We thus hypothesise that a high cholesterol diet induces or promotes the development of osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our clinical studies, we observed that postmenopausal women with hypercholesterolaemia showed increased bone Acta Pharmacologica Sinica npg turnover and lower BMD, which is consistent with the data reported in other clinical studies [2][3][4] . We thus hypothesise that a high cholesterol diet induces or promotes the development of osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
“…Femurs and 1-4 lumbar vertebrae (LV) were also excised. The whole left femur and lumbar vertebrae (1)(2)(3)(4) were used for further analysis. The bone mineral content and area was measured, and BMD was automatically calculated via dual-energy X-ray absorptiometry (HOLOGIC, MA, USA).…”
Section: Animals and Experimental Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were measured for serum total calcium (TCa), phosphate, glucose, creatinine, TC (TC), HDL-cholesterol (HDL-C), LDLcholesterol (LDL-C) (calculated using the friedewald formula), triglycerides, albumin, and total alkaline phosphatase by standard automated methods in a Technicon Dax autoanalyser (Technicon instruments, Co. USA). Hypercholesterolemia was defined as fasting serum TC levels greater than 220 mg/dL or an elevated serum LDL-C level greater than 140 mg/dL [26].…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Oxidized lipids, characteristic of hyperlipidemia, modulate the resorptive effects of parathyroid hormone (PTH) (17), inducing the expression of RANKL (18) and suppressing the differentiation of bone marrow stromal cells to osteoblasts (19). In this study, we sought to gain additional information beyond what has been reported so far (20)(21)(22) on bone mineral density among postmenopausal women with osteo-porosis based upon their history of statin use and fragility fractures. We conducted this test of the hypothesis because new preclinical evidence has been published recently, while clinical studies, especially on a population such as ours, are lacking.…”
Section: Introductionmentioning
confidence: 99%